#TITLE_ALTERNATIVE# - HARDIANANTO (NIM : 13707028); Dosen Pembimbing : Ir. Ahmad Nuruddin, M.Sc., Ph.D, NIKO
The use of magnetic recording medium in information technologies plays an important role for human life. Magnetic recording medium without overcoat layer is one of the challenges in this era. Magnetic material which had an excellent magnetic properties, hardness, and chemical stability is needed for created a magnetic recording medium without overcoat layer. One of the potential candidate material that could use as these application is barium ferrite (BaM). Barium ferrite thin film had been created using sol dip-coating method. Both of the precursor (barium nitrate and ferrite nitrate) solved into the ethylene glycol with Fe/Ba ratio = 11.5. Citric acid added as chelating agent with metal cation/ citric acid ratio = 1 : 2 into the precursor solution. Silicon (Si) substrate dipped into the sol with drawing speed 5 cm/minute, dried at 150oC, calcined at 900, 1000, and 1100oC in air, and calcined at 700, 800, dan 900oC in oxygen and carbon monoxide (flow rate = 2liter/ minute) separately, for 3 hours. BaM thin film polycrystal characterized using XRD, SEM, and VSM. As the result, the average size of particle diameter (d), length (l), and magnetic properties for BaM had increased from 900oC (80 nm, 276 nm, Ms, and Hci is about 0.00852 emu/cm2 and 2260 Oe) to 1000oC (96 nm, 304 nm, Ms, and Hci is about 0.0259 emu/cm2 dan 3840 Oe) and decreased in 1100oC (Ms dan Hci is about 0.0154 emu/cm2 dan 1480 Oe). Futhermore, it could be informed that calcination environment had a signifficant effect for cristallinity of BaM. Result from XRD, it was obtained that the content of BaM phase is about 29%wt, 43.7 %wt, and 18.6 %wt which calcined in air, oxygen, and carbon monoxide at 900oC, respectively.